Halide bridged organophosphorus complexes of HgX2 (X: I, Br and Cl): Synthesis, structure and theoretical studies - Mondal, Jahangir; Manna, Amit Kumar; Patra, Goutam Kumar (European Journal of Chemistry, 2021)
Three organophosphorus mercury (II) coordination compounds [Hg2(µ-X)2X2(PPh3)2] {X: I (1), Br (2), and Cl (3)} have been synthesized by the reaction of mercury (II) halides with triphenylphosphine. The prepared complexes were characterized by spectroscopic techniques as well as by elemental analysis. The crystal structure of [Hg2(µ-I)2I2(PPh3)2] (1) was obtained by single-crystal X-ray diffraction study. Crystal data for [Hg2(µ-I)2I2(PPh3)2], C36H30Hg2I4P2: Monoclinic, space group P21/c (no. 14), a = 19.2115(13) Å, b = 11.1291(8) Å, c = 19.0599(14) Å, β = 90.461(2)°, V = 4075.0(5) Å3, Z = 4, T = 293.15 K, μ (MoKα) = 10.657 mm-1, Dcalc = 2.336 g/cm3, 46095 reflections measured (4.23° ≤ 2Θ ≤ 49.994°), 7182 unique (Rint = 0.0563, Rsigma = 0.0365) which were used in all calculations. The final R1 was 0.0322 (I > 2σ(I)) and wR2 was 0.0780 (all data). The single crystal analysis of [Hg2(µ-I)2I2(PPh3)2] complex revealed that it has dimeric structure with bridged halides. [Hg2(µ-I)2I2(PPh3)2] complex has also a supramolecular arrangement through I···H-C interactions. The crystal packing and supramolecular features of these coordination compounds have also been studied using geometrical analysis, Hirshfeld surface analysis and DFT studies. Hirshfeld surface analysis indicated that H···H (49.3%), C···H (10.6%), and I···H (12.8%) interactions are the primary contributors to the intermolecular stabilization in the crystal. The equilibrium geometries of the studied complexes are investigated theoretically at the B3LYP/LANL2DZ level of theory. The calculated energy gap between HOMO-LUMO orbitals for complexes 1, 2, and 3 are in the trend of complex 3 > 2 > 1.